Drug Targeting Approaches and Use of Drug Delivery Systems in Management of Cancer - Ahuja, Alka; Narde, Gurpreet K.; Wadi, Nida M.A.; Meenakshi, Dhanalekshmi U. (Current Pharmaceutical Design, 2021)
Mutations and their manifestations in the form of various diseases and disorders result in cancer which is a major cause of human death worldwide. A considerable amount of information is available at the cellular, molecular and genetic levels regarding the occurrence and spread of precarious cancer; yet, there is no cure. The traditional methods of treatment such as chemotherapy, radiotherapy and surgical intervention have shown to be moderately effective and to keep some types of cancer under control, but each modality has its own advantages and disadvantages. In recent years, more advanced methods such as targeted therapies, immunotherapy, and precision medicine are shown to be promising, and these fields continue to expand rapidly along with the conventional methods. This review focuses on the reports of advanced methods of treatment from a scientific standpoint to recognize many new and modern approaches. Selective targeting of the tumour cells by nanoparticle-based novel drug delivery approaches includes the latest innovations in their preparation strategies and applications. The concept of precision medicine and its impact on treatment are highlighted here with the hope of individualised therapy with minimum side effects as a part of ever-expanding treatment strategies. Additional challenges related to cancer treatment like multi-drug resistance and toxicity are also deliberated in brief. Based on the available reports and scientific evidence, better targeted approaches with better quality clinical outcomes and more precise drug delivery to fit individual treatment needs are anticipated in the near future to control this deadly disease.
Keywords: toxicity